Developing Salesperson Performance: The Role of Customer Encountering Competence Portfolio, Relational Capital and Service Excellent Customer Heterogeneity - Retnawati, Berta Bekti; Nuryakin, Nuryakin (International Review of Management and Marketing, 2016)
The purpose of this study is to investigate the relationship of customer encountering competence portfolio, relational capital and service excellent customer heterogeneity to enhancing Indonesian pharmaceutical salesperson performance. The context is taken from pharmaceutical in Indonesia. The research setting was in a developing country, Indonesia, which has a promising pharmaceutical market in the global market. As a developing country that provides a large and growing market and is very potential in the global market, theories and measurements which have been conducted in the other countries need also to be done in Indonesia, as part of an effort to manage and enable the sales force to perform better in this global era. The sample of this study was tested with survey data from the detailers of the already go public pharmaceutical companies in Indonesia. The structural model analysis was employed to examine all the hypotheses. There were interesting finding in this study between customer encountering competence portfolio, relational capital and service excellent customer heterogeneityonsalesperson performance. The rejected hypothesis from the model, still leave a question over whether the customer encountering competence portfolio will enable salesperson performance. Therefore, there are many possible entry of intervening variables that could be considered to test the ability in customer encountering competence portfolio to enhancing the salesperson performance as recommendations for further research. Keywords: Customer Encountering Competence Portfolio, Relational Capital, Service Excellent Customer Heterogeneity, Salespersons Performance JEL Classification: M31